STRUCTURAL SEMANTIC AND STYLISTIC FEATURES OF MILITARY TERMS IN UZBEK AND ENGLISH LANGUAGES (Conference Zone, 2021)
Language is a major social weapon that forms social currents on a nationwide scale, preserves and transmits the culture, traditions, and social consciousness of a community that speaks the same language, thereby creating the basis for the emergence of nations. This article discusses the structural-semantic and stylistic features of military terms in Uzbek and English.